CULTURAL AND BIOCHEMICAL IDENTIFICATION OF ANTIBIOTIC-RESISTANT BACTERIA IN THE EARS OF DOGS AND PATIENTS WITH OTITIS EXTERNA - Ahmed Awad; Shaymaa Hassoon; Hiba Ali; Sarmad Mohammad (Archives of Veterinary Medicine)
Otitis externa is a common ear condition in humans and dogs caused by bacteria, fungus, yeasts, and ectoparasites. The aim of the study was molecular identification and sequencing of isolated antibiotic-resistant bacteria. The study consisted of 250 swab samples, with 100 samples from human patients and 150 from dogs. The samples were collected from October 2023 to January 2024 in Diyala Province. The isolates were identified using Vitek 2 depending on colony's color, form, and odor on study agar.  Biochemical tests were performed to identify the bacteria. DNA extraction and PCR were performed to confirm the identity of the bacterial isolates identified by the VITEK system. While VITEK provides preliminary identification based on biochemical tests, while molecular techniques such as PCR allow for more definitive confirmation of the species, particularly for identifying antibiotic-resistant strains. The study revealed that Staphylococcus spp. was the most common infection in humans, affecting 26.3% of cases, followed by Pseudomonas, Proteus, Escherichia coli, Streptococcus, Klebsiella, and Corynebacterium. Dog samples exhibited the highest infection rate of 26.7%, predominantly caused by Staphylococcus spp., followed by Streptococcus, Pseudomonas, Escherichia coli, Proteus, Klebsiella, Pasteurella species, and Corynebacterium respectively. Eight antibiotics were tested against these bacterial isolates using the disc-diffusion method, with all isolates showing susceptibility to Gentamycin, Ciprofloxacin, Tetracycline, and Amikacin. The investigation found two Staphylococcus aureus isolates OK 560669,1 and OK 9560670,1. Two GenBank entry numbers OK 560673,10 and OK 560674,1 were Escherichia coli isolates. Two Pseudomonas aeruginosa isolates with GenBank entries OK 560672,1 and OK 560671,1, were detected.